The Iww and the Workers Movement in Chile: The Case of the Northern Dockworkers (1919-1923) [la Iww y el Movimiento Obrero en Chile: El Caso de Los Obreros Portuarios Nortinos (1919-1923)] - Santibáñez-Rebolledo, C (Universidad de Tarapaca, 2018)
This paper seeks to dismantle the historiographical attribution that gives the Industrial Workers of the World (IWW) the organization and direction of the main strikes in the Chilean maritime terminals of Iquique and Antofagasta between 1919 and 1923. It is concluded that the role of this organization in the strike propensity of stevedores has been oversized by researchers. It is concluded that the role of this organization in the striking propensity of the dockworkers has been oversized by researchers, a problem that would be due to insufficient rigor in the treatment of documentation and labor terminology, as well as the lack of consideration of the conjuncture 1919-1923 as part of a long road that this workers had exhibited from the nineteenth century, particularly in regard to methods and demands. © 2018 Universidad de Tarapaca.